The Effect of Entrepreneurial Characteristics on the Performance of Aren Sugar Micro, Small and Medium Enterprises (MSMEs) in North Lombok Regency - Ratna Wati; St. Maryam; Adhitya Bagus Singandaru (Tinta Emas Institute, 2023)
This study aims to analyse the effect of entrepreneurial characteristics on performance in Aren Sugar micro, small and medium enterprises in North Lombok Regency. This research variable consists of 5 (five) independent variables, namely Self-Confidence (X1), Dare to Take Risks (X2), Commitment (X3), Work Ethic (X4) and Independence (X5) and 1 (one) dependent variable, namely Micro, Small and Medium Enterprises Performance (Y). The sample in this study were Aren Sugar business actors in the North Lombok Regency Region totalling 33 people. Using multiple linear regression analysis, the results showed that partially only the variables of Commitment and Independence had a significant influence on the performance of Aren Sugar MSMEs in North Lombok Regency as indicated by a p-value of 0.0128 and 0.0046 respectively. Meanwhile, the variables of Confidence, Dare to Take Risks, and Work Ethic do not have a significant effect on the performance of Aren Sugar MSMEs in North Lombok Regency. Based on the results of the F test, all variables together have a significant effect on the performance of MSMEs.